Deconstructing proton transport through atomically thin monolayer CVD graphene membranes. Issue 37 (17th May 2022) - Chaturvedi, Pavan; Moehring, Nicole K.; Cheng, Peifu; Vlassiouk, Ivan; Boutilier, Michael S. H.; Kidambi, Piran R.
Abstract : We deconstruct the origins of the orders of magnitude difference in proton conductance between micron and centimeter-scale monolayer graphene membranes to help advance atomically thin proton exchange membranes for applications in energy conversion, storage and separation. Abstract : Selective proton (H + ) permeation through the atomically thin lattice of graphene and other 2D materials offers new opportunities for energy conversion/storage and novel separations. Practical applications necessitate scalable synthesis via approaches such as chemical vapor deposition (CVD) that inevitably introduce sub-nanometer defects, grain boundaries and wrinkles, and understanding their influence on H + transport and selectivity for large-area membranes is imperative but remains elusive. Using electrically driven transport of H + and potassium ions (K + ) we probe the influence of intrinsic sub-nanometer defects in monolayer CVD graphene across length-scales for the first time. At the micron scale, the areal H + conductance of CVD graphene (∼4.5–6 mS cm −2 ) is comparable to that of mechanically exfoliated graphene indicating similarly high crystalline quality within a domain, albeit with K + transport (∼1.7 mS cm −2 ). However, centimeter-scale Nafion|graphene|Nafion devices with several graphene domains show areal H + conductance of ∼339 mS cm −2 and K + conductance of ∼23.8 mS cm −2 (graphene conductance for H + is ∼1735 mS cm −2 and for K + it is ∼47.6 mS cm −2 ). Using a mathematical-transport-model and Nafion filled polycarbonate track etched supports, we systematically deconstruct the observed orders of magnitude increase in H + conductance for centimeter-scale CVD graphene. The mitigation of defects (>1.6 nm), wrinkles and tears via interfacial polymerization results in a conductance of ∼1848 mS cm −2 for H + and ∼75.3 mS cm −2 for K + (H + /K + selectivity of ∼24.5) via intrinsic sub-nanometer proton selective defects in CVD graphene. We demonstrate atomically thin membranes with significantly higher ionic selectivity than state-of-the-art proton exchange membranes while maintaining comparable H + conductance. Our work provides a new framework to assess H + conductance and selectivity of large-area 2D membranes and highlights the role of intrinsic sub-nanometer proton selective defects for practical applications.